Monetary policy transmission through the bank financing channel: an analysis of bank heterogeneity in the context of dual banking system in Malaysia - Asbeig, Hussam; Kassim, Salina (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2014)
This study analyses the role of Islamic banks in transmitting monetary policy through the bank-financing channel in Malaysia. Bank size, liquidity and capitalization levels are expected to be the sources of cross-sectional differences among the banks. We evaluate a sample period from 2000 to 2011, using panel data with robust standard errors.